The Contribution of Treffinger's Learning Model to Students' Divergent Thinking Skills - Talib, Ahmad; Mytra, Prima (JTMT: Journal Tadris Matematika, 2023)
Research on the Treffinger Learning Model's contribution to students' divergent thinking ability is a quantitative pre-experimental study. The primary objective is to determine the impact of the Treffinger Learning Model on students' divergent thinking abilities. This research only involved one class that was given treatment without a control class. The population in this research were all grade VIII students of MTs Yasrib Limpomajang in the odd semester of the 2022/2023 academic year. The sampling method employed in this research is cluster random sampling. The instruments used for data collection were learning implementation observation sheets, student activity observation sheets, divergent thinking ability tests consisting of pretest and posttest. The data obtained were analyzed using descriptive and inferential statistical analysis. The results of descriptive statistical analysis indicate that before being taught using the Treffinger learning model, the average divergent thinking ability of students in the pretest was categorized as low. After undergoing learning with the Treffinger model, the average posttest divergent thinking ability increased to a good category. In conclusion, the Treffinger learning model contributes to the improvement of students' divergent thinking abilities in understanding numerical pattern material.